Gesteinsgebundene Gase in den Salzlagerstätten des Werra-Fulda-Kalireviers: Relevanz für die Lagerstättensicherheit und Einblick in die Bildung von Klimagasen und ozonzerstörenden Verbindungen bei Intraplattenvulkanismus [Forschungsdaten] - Schneider, Marcus (Universität, 2023)
The long mining history of the Werra-Fulda potash district is characterized by highly frequent gas-induced rocks burst during the extraction of potassium and magnesium salts. The gas was trapped by magmatic alterations of the Permian salt deposit during the Miocene Rhön volcanism. Large gas inclusions in the salt rocks pose a hazard to man and machinery during mining activities.
Gesehen am 12.06.2023
Keywords: Forschungsdaten; Datenbank